¿Cómo reconocer a un niño superdotado? Una guía para identificar, entender y educar a un niño de altas capacidades - Díaz Morales, Carolay Y. (2019)
Rarito, sabelotodo, cerebrito and other nicknames are often used to refer to gifted or high-ability individuals, who are not what people commonly assume them to be. Maite Garnica offers guidance and insight into the characteristics of gifted individuals. She explains that, although they do tend to have a high intelligence quotient, they are not necessarily geniuses, as is often believed. Children—and individuals in general—who possess high abilities tend to stand out in various domains and demonstrate a strong capacity for creativity.